Penerapan Metode Ripple Down Rules Untuk Mendiagnosa Penyakit Hamster - Sundari, Sri Putri (Building of Informatics, Technology and Science (BITS), 2020)
Hamsters are one of the many animals that are owned and are beginning to attract many people. Over time, hamsters began to be known as pets. Hamasters are also susceptible to disease. Diseases in hamsters and symptoms that cause very much, the problem now is not only need to know the cause of the disease but the important thing is to know quickly the disease suffered is also overcome so that the disease can be treated. Expert system which is one branch of artificial intelligence, capable of acting as experts in certain fields of study, researchers think animal health workers to help diagnose disease in hamsters as early as possible. The Ripple Down Rule (RDR) method is one method that has expert system inference / search capabilities and knowledge acquisition. By using RDR a system will be able to identify the disease as an expert with clinical symptoms such as input. The expert system for diagnosing disease in hamsters uses the Ripple Down Rules (RDR) method to explore the symptoms displayed in the form of questions in order to diagnose the type of hasmter's illness, to get results for treatment and to cure hasmter disease.